A Step Too Far? Whittington Hospital NHS Trust v XX [2020] UKSC 14. (22nd November 2020) - Horsey, Kirsty; Powell, Andrew
Abstract: This comment piece explores the decision in Whittington Hospital NHS Trust v XX [2020] UKSC 14. It argues that despite notable shifts in public policy in respect of the acceptability of surrogacy as a means of family formation in the past twenty years, the Supreme Court has taken a step too far in deciding that foreign commercial surrogacy is as widely socially accepted. This impacts on the reasonableness of any claim for damages in negligence for the costs of commercial surrogacy. It is posited that the issue of whether damages for foreign commercial surrogacy are reasonable or not will be the key battleground in future negligence cases of this type.